Primary Classes based on Media Technologies Represent an International Rating System for Teacher Control - Akhmedova, Malokhat (International Journal of Psychosocial Rehabilitation, 2020)
The modern period of the development of society is characterized by a strong influence of computer technologies on it, which penetrate into all spheres of human activity, ensure the dissemination of information flows in society, forming a global information space. An integral and important part of these processes is the computerization of education. At present, a new education system is being developed in The Republic of Uzbekistan, focused on entering the global information and educational space. This process is accompanied by significant changes in the pedagogical theory and practice of the educational process, associated with the introduction of adjustments to the content of teaching technologies, which should be adequate to modern technical capabilities, and contribute to the harmonious entry of the child into the information society. Computer technologies are called upon to become not an additional “appendage” in training, but an integral part of a holistic educational process, which significantly increases its effectiveness.